The Influence of LRC Current from the Q-Meter to the Measured Value of Dielectric Properties Within Radio Frequency Range - Harmen .; Armansyah H. Tambunan (PERTETA, 2003)
Various measurement method of dielectric properties has been studied by researches, one of wich is the Booton 160-A Q-meter operated within the radio frequency range. Determination of dielectric properties by the Q-meter is accomplised through the measurement of voltage (Q) and capacitance (C) of the LRC, which is naturally in the form of alternating current (AC). Measurement of the AC voltage by a voltmeter shows instability of the measured value, while using an osciloscope require an expensive apparatus. The problem seems can be solved by convertion of the LRC output from alternating to direct current. This paper is to study the influence of LRC output to the measured dielectric properties, by converting the output from alternating to direct current.